COMPARISON OF CVI AND HVT VACCINE STRAINS REPLICATION IN FEATHER TIPS IN DIFFERENT MAREK´S DISEASE VACCINATION PROGRAMS - MUNIZ, E. C.; ITO, D. T.; RODRIGUES, L. A.; SALLES, G. B. C.; KRAIESKI, A. L.; JUNIOR, D. V. NASCIMENTO; NETO, A. J. LIMA; FONSECA, A. S. K. (Ars Veterinaria, 2020)
Marek’s disease is an important neoplastic disease in birds caused by a serotype 1 specific herpesvirus; it is controlled by vaccination. In commercial breeders and layers in Brazil, current vaccination programs use the combination of attenuated or non-pathogenic strains of the HVT virus (turkey herpesvirus - serotype 3) and CVI 988 (Rispens - serotype 1). The combination of serotype 3 and 1 it has been an important and effective control strategy through the vaccination of long-lived birds. In addition, more recently the recombinant rHVT strain (vectorized vaccines) has been used in some vaccine programs. This study’s main objective was to compare CVI and HVT components’ replication in feather tips in three different Marek’s disease (MD) immunoprophylactic programs (T01 – program A, T02 – program B and T03 – program C). Quantification of these two vaccine strains was performed by real-time PCR in samples collected at the ages of 14, 21, and 28 days. At 14 days, mean of log[cvi] in program B was significantly higher than C (p<0.05). At 21 and 28 days, mean of log[cvi] of program C was significantly lower than A and B (p<0.05). For mean of log[hvt], at 28 days, program B was significantly higher than A (p<0.05). For proportion of positives, at 14 days, program B had 2.7 times more risk to be positive in CVI than program C (p<0.001). At 21 days, program B had 1.7 times more risk to be positive in CVI than program C (p=0.005). For HVT, at 28 days, program B had 3.2 times more risk to be positive than program A (p=0,009). Results showed significant differences between the treatments evaluated. In general the conventional combination Marek’s vaccine containing CVI+HVT (program B) showed higher replication rate and percentage of vaccine coverage than the programs with rHVT vector vaccines (program A and C).